A Quantum-Mechanical Looking Behind the Scene of the Classic G·C Nucleobase Pairs Tautomerization - Brovarets', Ol'ha O.; Muradova, Alona; Hovorun, Dmytro M. (Frontiers in Chemistry, 2020)
For the first time, at the MP2/6-311++G(2df,pd)//B3LYP/6-311++G(d,p) level of theory, a comprehensive quantum-mechanical investigation of the physico-chemical mechanism of the tautomeric wobblization of the four biologically-important G·C nucleobase pairs by the participation of the monomers in rare, in particular mutagenic, tautomeric forms (marked with an asterisk) was provided. These novel tautomeric transformations (wobblization or shifting of the bases within the pair) are intrinsically inherent properties of the G·C nucleobase pairs. In this study, we have obtained intriguing results, lying far beyond the existing representations. Thus, it was shown that Löwdin's G*·C*(WC) base pair does not tautomerize according to the wobblization mechanism. Tautomeric wobblization of the G*·C*(rWC) (relative Gibbs free energy ΔG = 0.00/relative electronic energy ΔE = 0.00 kcal·mol−1) (“r”—means the configuration of the base pair in reverse position; “WC”—the classic Watson-Crick configuration) and G*t·C*(H) (ΔG = −0.19/ΔE = 0.29 kcal·mol−1) (“H”—Hoogsteen configuration;”t” denotes the O6H hydroxyl group in the trans position) base pairs are preceded by the stages of the base pairs tautomerization by the single proton transfer (SPT). It was established that the G*t·C*(rH) (ΔG = 2.21/ΔE = 2.81 kcal·mol−1) base pair can be wobbled through two different pathways via the traditional one-stage mechanism through the TSs, which are tight G+·C− ion pairs, stabilized by the participation of only two intermolecular H-bonds. It was found out that the G·C base pair is most likely incorporated into the DNA/RNA double helix with parallel strands in the G*·C*(rWC), G·C*(rwwc), and G*·C(rwwc) (“w”—wobble configuration of the pair) tautomeric forms, which are in rapid tautomeric equilibrium with each other. It was proven that the G*·C*(rWC) nucleobase pair is also in rapid tautomeric equilibrium with the eight tautomeric forms of the so-called Levitt base pair. It was revealed that a few cases of tautomerization via the DPT of the nucleobase pairs by the participation of the C8H group of the guanine had occurred. The biological role of the obtained results was also made apparent.